A Comparative Study of Time Domain Compressed Sensing Techniques for Optoacoustic Imaging - Hirsch, Lucas (2022)
Speeding up data acquisition and reducing the complexity of the detection system are among the central goals for advancing optoacoustic imaging. In this way, new reconstruction algorithms using the compressed sensing (CS) formalism have received considerable interest in recent years. This work presents a comparative study of reconstruction algorithms using time-domain CS schemes for optoacoustic tomography. This is motivated by the well-known capabilities of the CS paradigm in achieving good reconstruction performance even with limited sensing capabilities. Formulation of the mathematical problem is provided along with simulation results, where the performance of different representation basis used in time-domain CS strategies are analyzed in a qualitative and quantitative fashion. Comparison with a well-established optoacoustic tomography reconstruction technique as backprojection is also provided. These experiments show the suitability of time-domain CS techniques for this application and point out that the use of the canonical basis for the representation of the optoacoustic measurements is well suited in comparison with other more sophisticated basis.